THE USE OF CADAVERS IN HUMAN ANATOMY CLASSES. TRADITIONAL METHOD, OUTDATED OR INDISPENSABLE? (Environmental Smoke, 2023)
Introduction: It is known that practical classes with a corpse awaken different feelings among students and it is common to observe behaviors of fear, disgust at the touch, anxiety, euphoria and/or deep respect. Records of corpse manipulations predate the sec. III a. Even so old, the dissected human body is still the most extraordinary, most complete and most complex resource among the tools currently used in teaching anatomy. Despite this, the use of cadavers in practical classes has been gradually replaced by other resources such as artificial models, even in medical graduation courses, raising discussions and calling into question the quality of training for new professionals. Objective: to analyze differences in the perception and quality of use of human anatomy content by students with and without the use of human cadavers in medical curricula. Methods: This study is a descriptive research, of the Integrative Literature Review (RIL) type. The search resulted in 21 articles, of which 10 articles form the corpus of this review. Results and Conclusion: Like a tree that bears sweet fruit, human dissection is always being stoned even by those who delight in its knowledge and secrets. Its importance surpassed fear, taboos, superstitions, dogmas, laws and time. It is indeed the basis of anatomical knowledge, resisting all adversities over time and remaining as the foundation of the training of health professionals from the most different segments.